Leaf Anatomy of the Thirteen Rare Plants in the Northeastern, Thailand - Senakun, Chadaporn; Somboonwattanakul, Issaraporn; Appamaraka, Sombat; Pasorn, Patana (Science Essence Journal, 2020)
บทคัดย่อ ศึกษากายวิภาคศาสตร์ใบของพืชหายากในภาคตะวันออกเฉียงเหนือ ประเทศไทย จำนวน 13 ชนิด 11 สกุล 9 วงศ์ โดยวิธีการลอกผิวใบ ย้อมด้วยสีซาฟรานิน และตัดตามขวางแผ่นใบและก้านใบด้วยเครื่องตัดเนื้อเยื่อแบบอัตโนมัติ (automatic plant microtome MT-3) ย้อมด้วยสีซาฟรานิน ผลการศึกษา พบลักษณะทางกายวิภาคศาสตร์ของพืชที่ศึกษา มีลักษณะเหมือนและแตกต่างกันของพืชในแต่ละวงศ์ที่มีการศึกษามาก่อน ได้แก่ รูปร่างของเซลล์ในเนื้อเยื่อชั้นผิวใบด้านบนและด้านล่าง ชนิดของปากใบ บริเวณที่พบปากใบ การมีหรือไม่มีขน รูปร่างตัดตามขวางของเส้นกลางใบและก้านใบ รูปร่างของเซลล์เนื้อเยื่อชั้นผิวใบตัดตามขวาง จำนวนชั้นของเซลล์แพลิเซด การมีหรือไม่มีผลึกและสารสะสม และบริเวณที่พบ การศึกษากายวิภาคศาสตร์ใบพืชหายากครั้งนี้ส่วนใหญ่เป็นรายงานครั้งแรก จึงสามารถนำมาเป็นข้อมูลเพิ่มเติมทางด้านกายวิภาคศาสตร์ของพืช ABSTRACT Anatomical study of rare plants in the northeastern, Thailand, 13 species 11 genera 9 families were investigated by using epidermal peeling stained with safranin and transverse of leaves by automatic plant microtome MT-3, stained with safranin. The results were found that leaf anatomical features in this study have similar and different characteristics with each the family that was reported in previous research. The analytical characteristics are shape of upper and lower epidermal cells, type of stomata, the distribution of stomata, presence/absence of trichome, shape of midrib and petiole, shape of epidermal cell with a cross-section, the number of palisade layers, the presence/absence of crystals and inclusion and the distribution of stomata. Most of the rare plant of this study were reported for the first time and can be used as additional information to provide a generic description of plant anatomy.